1998
DOI: 10.1097/00005344-199800001-00120
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Endothelin-1 and Endothelin-Converting Enzyme-1 mRNAs and Proteins in Failing Human Hearts

Abstract: Accumulating evidence suggests that endogenous endothelin-1 (ET-1) may contribute to the development of heart failure. In this study we determined sites of ET-1 synthesis and production in the failing human myocardium by immunohistochemistry and in situ hybridization for ET-1 and endothelin-converting enzyme-1 (ECE-1). Myocardial tissues were obtained from 19 patients with heart failure and from four noncardiac patients as controls. In both failing and nonfailing hearts, apparent immunoreactivity for ET-1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 13 publications
4
20
0
1
Order By: Relevance
“…20 Importantly, the potentiation of exogenous and endogenous ET-1 effects seen in endotoxemia appeared to be unrelated to alteration in ET A receptor density or sensitivity. Our study also confirmed sepsis-induced increases in plasma ET-1 concentration as previously described 21,22 and showed that septic heart was unlikely to be the source of increased ET-1 production, because a similar pattern of ET-1 staining was found in control and septic hearts.…”
Section: Discussionsupporting
confidence: 91%
“…20 Importantly, the potentiation of exogenous and endogenous ET-1 effects seen in endotoxemia appeared to be unrelated to alteration in ET A receptor density or sensitivity. Our study also confirmed sepsis-induced increases in plasma ET-1 concentration as previously described 21,22 and showed that septic heart was unlikely to be the source of increased ET-1 production, because a similar pattern of ET-1 staining was found in control and septic hearts.…”
Section: Discussionsupporting
confidence: 91%
“…Preproendothelin-1 has been more extensively studied and documented in vascular endothelial cells, as well as smooth muscle cells, heart, lung, kidney, brain, and skin (27)(28)(29). Increased endothelin expression has been reported in pulmonary hyper- tension (36), myocardial ischemia (37), and congestive heart failure (38). These are conditions associated with elevated elastase activity where it would be advantageous to assess the possible protective effects of very high levels of elafin expression.…”
Section: Discussionmentioning
confidence: 99%
“…and endothelial cells, and cardiomyocytes express high affinity ET-1 binding sites [4,5,6]. ET-1 induces contraction and increases inotropy of cardiomyocytes.…”
Section: Immunohistologymentioning
confidence: 99%